The effect of medical informatics training on students' knowledge and attitude to use it in future medical work: a comparative study among Saudi medical students (Bangladesh Journal of Medical Science, 2025)
Introduction The integration of medical informatics (MI) in medical education is crucial for preparing future healthcare professionals to effectively utilize technology in their practice. This study aimed to investigate the impact of MI training on Saudi medical students’ knowledge and attitude towards using technology in future medical practice. Method A cross-sectional descriptive study was conducted among medical students at Saudi medical universities, employing a non-probability convenience sampling method. A standard pre-structured, self-reported questionnaire was used to collect data from 1508 students, with 1192 having undertaken an MI course and 316 not having undertaken the course. The validated questionnaire included two dimensions of knowledge and attitude and each dimension had 12 items. Results The mean scores of knowledge and attitude towards MI were significantly higher among students who had undertaken the MI course compared to those who had not (p < 0.001). The results highlighted the effectiveness of MI training in enhancing students’ understanding of various MI concepts and applications, including electronic medical records, patient confidentiality, clinical decision support systems, telemedicine, e-prescriptions, evidence-based practice, and legal/ethical considerations in clinical informatics. Conclusion This result of this study highlights the significance of MI course in shaping students’ perceptions and understanding of various aspects of healthcare, particularly in the context of EMRs, patient confidentiality, and the role of technology in healthcare. The findings provide valuable insights into the transformative impact of MI training on students’ knowledge and attitude towards utilizing informatics in their future medical careers.BJMS, Volume: 24. Supplementary Issue 2025, Page : 170-177